2014
DOI: 10.1007/s13365-014-0267-1
|View full text |Cite
|
Sign up to set email alerts
|

Form follows function: astrocyte morphology and immune dysfunction in SIV neuroAIDS

Abstract: Cortical function is disrupted in neuroinflammatory disorders, including HIV-associated neurocognitive disorders (HAND). Astrocyte dysfunction includes retraction of foot processes from the blood-brain barrier and decreased removal of neurotransmitters from synaptic clefts. Mechanisms of astrocyte activation, including innate immune function and the fine neuroanatomy of astrocytes, however, remain to be investigated. We quantified the number of GFAP-labeled astrocytes per mm2 and the proportion of astrocytes i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(38 citation statements)
references
References 49 publications
(76 reference statements)
1
37
0
Order By: Relevance
“…In the same way that neuronal dendrites are adaptable and respond to changes in CNS activity by altering their structure, astrocytic processes dynamically alter their morphology and interact with synapses in response to their environment [75] . Morphological changes in astrocytes have been documented in chronic stress [76] , traumatic brain injury [77] , neurodegenerative disease [78] , CNS viral and bacterial infections [79,80] , and behavioral and mood disorders [81,82] . Experimentally, changes in astrocyte morphology have been reported after ethanol administration [83] , dietary-induced obesity [84] , and physical exercise [85] .…”
Section: Morphologymentioning
confidence: 99%
See 2 more Smart Citations
“…In the same way that neuronal dendrites are adaptable and respond to changes in CNS activity by altering their structure, astrocytic processes dynamically alter their morphology and interact with synapses in response to their environment [75] . Morphological changes in astrocytes have been documented in chronic stress [76] , traumatic brain injury [77] , neurodegenerative disease [78] , CNS viral and bacterial infections [79,80] , and behavioral and mood disorders [81,82] . Experimentally, changes in astrocyte morphology have been reported after ethanol administration [83] , dietary-induced obesity [84] , and physical exercise [85] .…”
Section: Morphologymentioning
confidence: 99%
“…Atrophic astrocytes result in reduced support for neuronal networks, which may ultimately decrease neuronal connectivity and plasticity. We have recently shown that, in the setting of simian immunodeficiency virus (SIV) infection and SIV-induced encephalitis, gray and white matter astrocytes retract their processes resulting in an overall decreased arbor irrespective of encephalitic status [79] . It is hypothesized that reduced numbers of astrocytes is directly linked to disruptions in cognitive behavior and that astrocyte loss may be a primary driver of pathology [100,101] .…”
Section: Astrocyte Atrophymentioning
confidence: 99%
See 1 more Smart Citation
“…At the same time, research in an SIV model showed that infected astrocytes shows changes in morphology, namely decreased arborization and dendritic length in both white and grey astrocytes. This suggests that infected astrocytes may create interruptions in glialneuronal signaling, leading to brain atrophy and the symptoms associated with HAND (72). A synthesis of these findings may indicate that astrocytes are not simply passively infected, but in fact attempt to rid the brain of HIV only to fall prey to HIV.…”
Section: Introductionmentioning
confidence: 99%
“…It could be speculated that binding of the anti-GLAST 152-172 antibody on the extracellular surface of the astrocytes induces a signal that results in the rearrangement of GFAP within the cell. In addition, it has recently been reported that immune activation of astrocytes is linked to altered cortical astrocyte morphology, as identified by GFAP staining, in an infection model (Lee et al, 2014). Therefore, even though some of the astrocytes in the cultures treated with anti-GLAST 152-172 antibody plus complement were not killed, the resulting observations suggest that the antibody did indeed have some potentially pathogenic effects on the astrocytes.…”
Section: A Lower Left Panel)mentioning
confidence: 96%